Selected Tools for Measuring Innovation - Wodecka-Hyjek, Angelika (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The aim of this paper is to organise and present a number of tools for measuring innovation in the field: the economies of nations, enterprises and public sector organisations. The first part of the paper presents definitions of innovation based on the professional literature. The main part then describes selected tools for measuring innovation in four fields: national economies, using the Summary Innovation Index (SII) and Innovation Barometer (Innobarometer - INN); enterprises, using the work of A. Pomykalski, Boston Consulting Group and L. Białoń; public sector organisations, using a model designed by the PUBLIN Project; model measures of the diffusion of innovations by R. M. Walker, C. N. Avellaneda and F. S. Berry. The final part of the paper articulates problems in measurement highlighted regardless of the context of the study and the difficulties in designing a universal tool.